Effect of Bedincak and PGRI Gymnastics Exercises on Motor Development - Donny Firmansyah; Rumini Rumini; Bambang Priyono (STKIP Muhammadiyah Kuningan, 2022)
The purpose of this study was to identify and analyze the differences in the effects of the Pgri bedincak gymnastic exercises for gross motor development, to analyze the differences in the impact of male and female gross motor skills, analyze the interactions of gymnastics and gross motor development between the sexes, and the Bedincak and PGRI exercises on gross motor development for male, female students. This study used an experimental method with a 2x2 factorial design. The data analysis technique used analysis of variance (ANOVA) at the significance level (> 0.05). The population is in grade 6 elementary school aged 11-16 years in Simpang Rimba District as many as 472 people. The sampling technique was a purposive sampling of 60 people. The results of this study: Based on the analysis of the study, it was found that the Bedincak Gymnastics and PGRI Gymnastics exercises are good exercises because they can affect the agility, coordination, balance and speed of both male and female students on gross motor development. So it can be concluded that there are differences in the effect of Bedincak and PGRI Gymnastics Exercises on Male and Female Gender Gross Motor Development, and there is no interaction between the Effects of Bedincak and PGRI Gymnastic Exercises on Gross Motor Development in Male and Female Students.